No b.s. time management for entrepreneurs : the ultimate no holds barred kick butt take no prisoners guide to time productivity and sanity - Kennedy, Dan S. (Gildan Audio, 2019)
WARNING: This book is not for the faint of heart, fawningly polite, or desperate to be liked. This book is expressively for entrepreneurs and business owners who wear many hats-those who can't resist piling more responsibility onto his own shoulders, who has more great ideas that time and resources to take advantage of them, who runs (not walks) through each day. Your time is incredibly valuable to you, and you are constantly "running out of it." Serial entrepreneur Dan S. Kennedy delivers a fresh take on the mantra "time is money" as he shows you how to drastically re-engineer your entire relationship with time and, if applied faithfully, achieve peak personal productivity and make lots and lots of money. Learn how to: accurately calculate the value of your time-and put a meter on those consuming it; slay time vampires; stop "productivus interruptus"--Master the five time-defense tactics; achieve maximum productivity with Psycho-Cybernetics; The 8 No B.S. Time Truths never to violate despite the conspiracy against them; Become successful beyond your wildest dreams-apply the #1 most powerful personal discipline; the 10 time management techniques worth using. Only 10!; and Fire yourself! Replace yourself. Make more money from less time, and have more freedom to do big things!